Moisture Stability of Sulfide Solid-State Electrolytes - Yersak, Thomas A.; Zhang, Yubin; Hao, Fang; Cai, Mei (Frontiers in Energy Research, 2022)
In this report we detail a comprehensive study on the moisture stability of sulfide solid-state electrolytes in dry room environments. Although sulfide SSEs have many favorable attributes, this class of materials suffers from poor stability with water. Sulfide SSEs react with water to form gaseous H2S and a variety of solid byproducts like Li3PO4 and LiOH, which go on to increase the interfacial impedance of solid-state batteries. Lab-scale research typically utilizes gloveboxes with < 1 ppm water, however, the large-scale manufacturing of Li-ion batteries occurs in -40 °C dewpoint dry rooms with around 126 ppm water. Consequently, the moisture stability of sulfide SSEs must be addressed if the manufacture of solid-state batteries based on sulfide SSEs is to be scaled up. Here, we are the first to characterize the moisture stability of sulfide SSEs according to both H2S and the degradation of ionic conductivity at different moisture setpoints ranging from -76 °C to -40 °C dewpoint. A variety of different SSE compositions are studied; namely, (Li2S)75(P2S5)25, (Li2S)70(P2S5)30, (Li2O)7(Li2S)68(P2S5)25, (Li2O)7(Li2S)63(P2S5)30, and (Li2S)75(P2S5)25 + 20 mol% LiI. We find that moisture stability improves with 75 mol% Li2S modifier content and the introduction of a Li2O co-modifier. After a 30 minute exposure in a -40 °C dewpoint dry room environment we found that (Li2S)75(P2S5)25 + 20 mol% LiI powder generated 0.1 cc/g H2S and its ionic conductivity decreased by over 50%. However, when SSE powder was exposed as a slurry in a dodecane carrier the same SSE composition generated 0 cc/g H2S and its ionic conductivity only dropped by 14%. Our results show that sulfide SSEs have acceptable moisture stability when appropriately processed in a dry room environment.